Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

If [tex]\alpha[/tex] and [tex]\beta[/tex] are zeros of the quadratic polynomial [tex]5x^2 + 5x + 1[/tex], then the value of [tex]\alpha^{-1} + \beta^{-1}[/tex] is:

Sagot :

Certainly! Let's solve the given problem step-by-step.

Given the quadratic polynomial [tex]\(5x^2 + 5x + 1\)[/tex], we need to find the value of [tex]\(\alpha^{-1} + \beta^{-1}\)[/tex] where [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex] are the roots of this polynomial.

### Step 1: Understand Vieta's formulas

For a quadratic polynomial of the form [tex]\(ax^2 + bx + c = 0\)[/tex], Vieta's formulas tell us two key relationships between the coefficients of the polynomial and its roots. If [tex]\(\alpha\)[/tex] and \beta are the roots, then:
1. [tex]\( \alpha + \beta = -\frac{b}{a} \)[/tex]
2. [tex]\( \alpha \beta = \frac{c}{a} \)[/tex]

### Step 2: Apply Vieta's formulas to our polynomial

Here, [tex]\(a = 5\)[/tex], [tex]\(b = 5\)[/tex], and [tex]\(c = 1\)[/tex]. Using Vieta's formulas, we can find the sum and product of the roots [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex]:

1. The sum of the roots:
[tex]\[ \alpha + \beta = -\frac{b}{a} = -\frac{5}{5} = -1 \][/tex]

2. The product of the roots:
[tex]\[ \alpha \beta = \frac{c}{a} = \frac{1}{5} \][/tex]

### Step 3: Calculate [tex]\(\alpha^{-1} + \beta^{-1}\)[/tex]

We know:
[tex]\[ \alpha^{-1} + \beta^{-1} \][/tex]

This expression can be rewritten in terms we already have:
[tex]\[ \alpha^{-1} + \beta^{-1} = \frac{1}{\alpha} + \frac{1}{\beta} = \frac{\alpha + \beta}{\alpha \beta} \][/tex]

Using the values from Vieta's formulas:
- [tex]\(\alpha + \beta = -1\)[/tex]
- [tex]\(\alpha \beta = \frac{1}{5}\)[/tex]

Plugging these values into the equation:
[tex]\[ \alpha^{-1} + \beta^{-1} = \frac{\alpha + \beta}{\alpha \beta} = \frac{-1}{\frac{1}{5}} = -1 \times 5 = -5 \][/tex]

### Final Answer

Hence, the value of [tex]\(\alpha^{-1} + \beta^{-1}\)[/tex] is [tex]\(-5\)[/tex].